PENGEMBANGAN SISTEM DETEKSI OVER-HEIGHT VEHICLE BERDASARKAN GEOMETRI KAMERA - Yusron Rijal; Himayatul Millah (STMIK YADIKA BANGIL, 2019)
At this time, many Overh-Height Vehicle Detection Systems have been developed to help reduce the risk of road accidents, especially vehicles which exceeds the height limit for the bridge. In the research that the author did was Development of Detection Systems Camera Geometry Based Overh-Height Vehicle, the method developed in this study is the implementation of the camera's geometry position to detect over-height vehicle. Modifications are made by changing the tilt angle camera with a height of 2 meters, 2.5 meters and 3 meters with the choice of ROI area so that it is expected to increase the accuracy of over-height detection vehicle.The detection phase is carried out through the process of motion detection and processing image that is get RGB, RGB2Gray, thresholding, morphology is dilated with 4x4 kernel to detect objects that exceed the limit or touch the ROI line. The results obtained from this study are, data processing uses high a 2.5 meter camera is able to produce more optimal data with a total of 84 frames are saved, 84 frames are detected correctly, 2 frames are detected incorrectly and level 97.67% accuracy. Keywords: Over-Height Vehicle, Detection System, Camera Geometry